FACTORS THAT ENCOURAGE BUGIS COMMUNITIES MAINTAINING GREEN OPEN SPACES - Mithen Lullulangi; Muhammad Ardi; Bakhrani Abdul Rauf; Rahmansah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Green open space is open space used for plants or plants naturally or plant cultivation, which has an ecological function, is the ’lungs’ of a city or region because plants and green plants can absorb carbon dioxide (CO2) levels, add oxygen, reduce the temperature with shade and coolness of plants, become water catchment areas, and reduce noise so it needs to be maintained. This study aims to find out how the knowledge of ecosystem factors, attitude factors towards the environment, motivational factors, and local wisdom factors can encourage the Bugis community to manage green open space. Research sites are in the districts of Bone, Soppeng, and Wajo. Respondents of the study, as many as 300 families, namely 100 households in each district, were chosen randomly. Data collection techniques are questionnaires and data analysis techniques with descriptive analysis. The results showed that: (1) Ecosystem knowledge factor (X1) drives in the medium category, (2) environmental care attitude factor (X2) is a positive category, (3) Motivation factors maintain the environment (X3) is medium category, and (4) local wisdom factor (X4) is a medium category. The results of this study, are expected to be useful for scientists or environmentalists in this area, as a reference material to increase understanding for the Bugis community in particular, and the public about how important it is to support green open spaces as one of the important elements in urban areas.